Study of the glassy magnetic behaviour and charge-ordering phase transitions in La0.75Ca0.25FeO3−δ perovskite. Issue 16 (3rd June 2017) - Abdel-Khalek, E. K.; Mohamed, E. A.; Salem, A. F.
Abstract: In this work, La0.75 Ca0.25 FeO3−δ perovskite sample was prepared by the coprecipitation method. The nanoparticle was found to crystallize in the orthorhombic (Pbnm) phase as confirmed by X-ray diffraction (XRD) and transmission electron microscopic (TEM). The oxygen non-stoichiometry (δ) and magnetic states of iron ions (three magnetic sextets and non-magnetic doublet) were investigated by Mössbauer spectroscopy at room temperature (RT). The shape of the magnetic hysteresis loop of the sample reveals the existence of a weak ferromagnetism at RT. The magnetization vs. temperature curves, measured in the 9 to 200 K range, showed that the sample exhibits two magnetic-phase transition temperatures at 29 K (Tg ) and 120 K (TCO ). The magnetization isotherms, M (H), around these magnetic-phase transition temperatures for the sample are analyzed.